Faktor-Faktor yang Berhubungan dengan Kinerja Pekerja Perempuan di PT Telkom Indonesia Witel Jakarta Timur Tahun 2023 - Syifa Nindita Rizkadewi (2023)
Female workers as human resources are required with an additional workload to achieve company targets. Additional workload certainly affects the lives of women workers physically and mentally, including the performance of the women workers themselves. This study aims to analyze the factors related to the performance of female workers at PT Telkom Indonesia Witel East Jakarta in 2023. This research is a quantitative analytic study with a cross-sectional design and a sample size of 120 female workers obtained from the Lemeshow formula. The measurement tools used are the Individual Work Performance Questionnaire (IWPQ), NASA-TLX (Task Load Index), body mass index, and individual characteristics questionnaires. The results showed that there was no relationship between age (p-value=0.836), education (p-value=0.108), marital status (pvalue=0.513), years of service (p-value=0.445 ), nutritional status (p-value=0.895), and mental workload (p-value=0.935) with the performance of female workers at PT Telkom Indonesia Witel East Jakarta in 2023. This study concluded that age, education, marital status, work, nutritional status, and mental workload factors have no relationship with the performance of female workers at PT Telkom Indonesia Witel Jakarta Timur in 2023. Workers are advised to be able to plan, organize, and prioritize work so that work is more effective and efficient. Companies can also form collaboration teams for workers to get together and share knowledge, experiences and perspectives.